High-CO(2) Treatment Prolongs the Postharvest Shelf Life of Strawberry Fruits by Reducing Decay and Cell Wall Degradation - Eum, Hyang-Lan (Foods, 2021)
Improved methods are needed to extend the shelf life of strawberry fruits. The objective of this study was to determine the postharvest physiological mechanism of high-CO(2) treatment in strawberries. Harvested strawberries were stored at 10 °C after 3 h of exposure to a treatment with 30% CO(2) or air. Pectin and gene expression levels related to cell wall degradation were measured to assess the high-CO(2) effects on the cell wall and lipid metabolism. Strawberries subjected to high-CO(2) treatment presented higher pectin content and firmness and lower decay than those of control fruits. Genes encoding cell wall-degrading enzymes (pectin methylesterase, polygalacturonase, and pectate lyase) were downregulated after high-CO(2) treatment. High-CO(2) induced the expression of oligogalacturonides, thereby conferring defense against Botrytis cinerea in strawberry fruits, and lowering the decay incidence at seven days after its inoculation. Our findings suggest that high-CO(2) treatment can maintain strawberry quality by reducing decay and cell wall degradation.